Reducing Youth Access to Alcohol: Findings from a Community‐Based Randomized Trial. Issue 1 (12th June 2012) - Flewelling, Robert L.; Grube, Joel W.; Paschall, M. J.; Biglan, Anthony; Kraft, Anne; Black, Carol; Hanley, Sean M.; Ringwalt, Christopher; Wiesen, Chris; Ruscoe, Jeff
Abstract: Underage drinking continues to be an important public health problem and a challenge to the substance abuse prevention field. Community‐based interventions designed to more rigorously control underage access to alcohol through retailer education and greater enforcement of underage drinking laws have been advocated as potentially effective strategies to help address this problem, but studies designed to evaluate such interventions are sparse. To address this issue we conducted a randomized trial involving 36 communities to test the combined effectiveness of five interrelated intervention components designed to reduce underage access to alcohol. The intervention was found to be effective in reducing the likelihood that retail clerks would sell alcohol to underage‐looking buyers, but did not reduce underage drinking or the perceived availability of alcohol among high school students. Post hoc analyses, however, revealed significant associations between the level of underage drinking law enforcement in the intervention communities and reductions in both 30‐day use of alcohol and binge drinking. The findings highlight the difficulty in reducing youth drinking even when efforts to curtail retail access are successful. Study findings also suggest that high intensity implementation of underage drinking law enforcement can reduce underage drinking. Any such effects of enhanced enforcement on underage drinking appear to be more directly attributable to an increase in perceived likelihood of enforcement and the resultant perceived inconveniences and/or sanctions to potential drinkers, than to a reduction in access to alcohol per se.